Challenges in property valuation in Sub-Saharan Africa: A systematic review - Becsky-Nagy, Patrícia; Sachicola, Victor Dario (Vezetéstudomány / Budapest Management Review, 2025)
Rapid demographic and urban transitions in the Sub-Saharan Africa (SSA) region are reshaping the demand for land, housing, and infrastructure. In this evolving context, property valuation is essential for real estate development, investment decisions, and economic planning. The article examines what factors influence property valuation practices in SSA, what the key challenges are, and what the differences are between valuation methods in SSA vs. developed economies. This study applies the PRISMA-based Systematic Literature Review (SLR) method to examine 25 peer-reviewed articles published between 2010 and 2024. To enrich the review with empirical insight, a correlation analysis was conducted using macroeconomic indicators. Findings reveal fragmented valuation systems, institutional inefficiencies, and informal land markets that distort property investment. The study recommends regulatory reform, data standardization, and digital valuation tools to improve transparency and market reliability across SSA’s real estate sector.